2009
DOI: 10.1111/j.1360-0443.2008.02472.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of work‐place interventions for alcohol‐related problems

Abstract: The literature review revealed few methodologically adequate studies of work-place alcohol interventions. Study designs, types of interventions, measures employed and types of work-places varied considerably, making comparison of results difficult. However, it appears from the evidence that brief interventions, interventions contained within health and life-style checks, psychosocial skills training and peer referral have potential to produce beneficial results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 26 publications
2
88
0
3
Order By: Relevance
“…For example, studies have shown that workplace programs have the potential to support change in drinking norms and reduction of harmful drinking (e.g., Webb, Shakeshaft, Sanson-Fisher, & Havard, 2009), and that even brief interventions for harmful alcohol consumption have the potential to reduce alcohol intake (Kaner et al, 2007;Vasilaki, Hosier, & Cox, 2006). As a part of this strategy, special attention needs to be paid to treatment barriers that have been described in many other studies, such as concerns about privacy, social ------IJADR 7(1) ------stigma, and lack of social support systems (e.g., Grella & Stein, 2013;Schomerus et al, 2011;Schmidt & Room, 1999;Yap et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have shown that workplace programs have the potential to support change in drinking norms and reduction of harmful drinking (e.g., Webb, Shakeshaft, Sanson-Fisher, & Havard, 2009), and that even brief interventions for harmful alcohol consumption have the potential to reduce alcohol intake (Kaner et al, 2007;Vasilaki, Hosier, & Cox, 2006). As a part of this strategy, special attention needs to be paid to treatment barriers that have been described in many other studies, such as concerns about privacy, social ------IJADR 7(1) ------stigma, and lack of social support systems (e.g., Grella & Stein, 2013;Schomerus et al, 2011;Schmidt & Room, 1999;Yap et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Workplaces provide an inimitable advantage to access difficult to reach and high risk populations, such as young males and high risk drinkers [46]. In a literature review of ten papers analyzing the effectiveness of workplace intervention strategies, Webb et al [46] found seven studies with significant reductions in alcohol consumption or related problems.…”
Section: Workplace Intervention and Wellness Programsmentioning
confidence: 99%
“…In a literature review of ten papers analyzing the effectiveness of workplace intervention strategies, Webb et al [46] found seven studies with significant reductions in alcohol consumption or related problems. Hermansson et al [47] found considerably positive results of a routine health and lifestyle check-up including alcohol screening at a large transport company.…”
Section: Workplace Intervention and Wellness Programsmentioning
confidence: 99%
“…Coloca-se, de imediato, o difíc il acesso a grandes grupos de participantes, bem como a obtenção de respostas fidedignas, principalme nte se as drogas ilícitas entrarem no estudo. Verifica-se a dificuldade de realização de estudos longitudinais, ou de ensaios clínicos randomizados com alcoolistas (Webb et al, 2009).…”
unclassified